Educational Philosophy of Swami Vivekananda - VIKRANT MISHRA (Dr. Chinmay Pandya, 2014)
Swami Vivekananda has said that education is the manifestation of the perfection already present in man. Through Vivekananda's life experiences, he learned many truths and shared them with others. These truths addressed the subject of education. To him education played and plays a vital role in curing the evils in society, and it is critical in shaping the future of humanity. He talked about "man-making" education. In Vivekananda's educational scheme for India, the uplift of women and the masses received the highest priority. In this paper, a systematic attempt has been to explain the educational philosophy of Swami Vivekananda.